PENDIDIKAN POLA ASUH KELUARGA BERBASIS MASYARAKAT - Yulastri Arif; Dewi Murni; Zifriyanthi Minanda Putri (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Andalas, 2018)
The problem of families of traditional fishermen in Ulak Karang Selatan district is the highnumber of child victims of violence (98%) and 80% of perpetrators of violence are family. Thecause is the wrong perception of how to educate children. The goal is to form family andconscious counselors. Activities carried out from 5 September to 18 October 2017 include:screening families at risk of violence, education and the formation of child aware families andtraining of child conscious child counselors. The result is 76 families that become consciousfamily of 49 families in Ulak Karang Selatan subdistrict and 27 families in Ulak Karang Utarasubdistrict of North Padang subdistrict which has been dsikrining as family at risk of violence.The 76 families showed an increase in cognition and affection about parenting, how to detectchildren as victims of violence, how to prevent violence and how to handle child victims ofviolence with a low average of 40.5 to 80.83, while the average affection score increased fromthe average lowest 37.00 to 64.00. Based on the result of cognitive and affective improvement,10 counselors of Conscious Children's Family are 6 counselors in Ulak Karang Selatan and 4counselors in Ulak Karang Utara village. Recommendation of the need for further training ofchild conscious child counselors in the context of establishing kelurahan child affection so thatthe target of health promotion achievement can be improved.